Spatial competition on rural bank efficiency: Evidence from Indonesia - Citra Amanda (Cogent Economics & Finance, 2023)
This study empirically examines bank spatial competition within the rural banking setting of Indonesia. The specific focus is on bank cost efficiency. It presents a new competition measure based on two spatial variables: physical distances and Thiessen polygon market boundaries. This study uses panel data from a large sample of more than 1,000 rural banks using quarterly financial data of rural banks in Indonesia from Q1-2014 to Q4-2018. Parametric or stochastic frontier analysis of Model EN is used to handle the endogeneity in bank cost efficiency measurement. The results show that bank efficiency is higher for shorter distances between banks and larger boundaries. Overall, the results support the competition-efficiency hypothesis. It also helps the idea that banks have mark-up pricing (higher market power) and may choose to reduce their effort to maximize profit.
Keywords: R12; G21; G28; O18; 330; bank cost efficiency; market boundaries; Physical distance; rural banks; SFA model